SEMANTIC CHARACTERISTICS OF NOUNS IN THE ENGLISH LANGUAGE - Elmurodova Nozima Sherzod kizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract.  Nouns  represent  one  of  the  core  lexical  categories  in  the  English language and play a central role in meaning construction and reference. This article examines the semantic characteristics of English nouns, focusing on their conceptual, functional,  and  classificatory  features.  Special  attention  is  given  to  semantic distinctions such as concreteness and abstractness, countability, animacy, proper and common  reference,  and  semantic  extension  through  metaphor  and  metonymy.  The study also considers the role of nouns in lexical relations and discourse organization.